Face 2 Face Upper Intermidiate. Workbook - Tims, Nicholas and Bell, Jan (Cambridge Cambridge University Press, 2007)
Face 2 Face is a general English course for adults and young adults who want to learn how to communicate quickly and effectively in todas world. Based on the communicative approach, it combines the best in current methodology with special new features designed to make learning and teaching easier. Vocabulary and grammar are given equal importance and there is a strong focus on listening and speaking in social situations.
Keywords: English Practice